Anti-Inflammatory Effects of a Polyphenols-Rich Extract from Tea (Camellia sinensis) Flowers in Acute and Chronic Mice Models. (30th July 2012) - Chen, Bang-Tian; Li, Wei-Xi; He, Rong-Rong; Li, Yi-Fang; Tsoi, Bun; Zhai, Yu-Jia; Kurihara, Hiroshi
Abstract : While beneficial health properties of tea leaves have been extensively studied, less attention is paid to the flowers of tea. In this study, the anti-inflammatory effects of hot water extract of tea ( Camellia sinensis ) flowers were investigated. Pharmacological studies found that administration of tea flowers extract (TFE) could effectively inhibit croton oil-induced ear edema and carrageenin-induced paw edema. Furthermore, administration of TFE also protected against Propionibacterium acnes ( P. ances ) plus lipopolysaccharide-(LPS-) induced liver inflammation by reversing the histologic damage and plasma alanine aminotransferase (ALT) increase. Moreover, the levels of nitric oxide (NO), tumor necrosis factor-(TNF)- α and interleukin-(IL-) 1 β mRNA in mouse liver were markedly suppressed after treatment with TFE in mice with immunological liver inflammation. These results indicated that tea flowers had potent anti-inflammatory effects on acute and immunological inflammation in vivo, and may be used as a functional natural food.